Evaluating Decision-Making Capacity: An Introductory Curriculum for Medical Students and Residents - Amber Frank (Association of American Medical Colleges, 2015)
Abstract Introduction This goal of this curriculum is to introduce medical students and residents to the essential components of evaluating decision-making capacity in their patients, and to provide them with opportunities to practice their understanding of these principles through sample cases. Methods The curriculum includes a primer on concepts to provide a general introduction to the topic, sample cases to illustrate important concepts, and a case discussion guide reviewing key points brought up by each case. The curriculum as a whole is designed for use as an instructor-guided, problem-based learning module, in which basic concepts are first reviewed as a large group and then put into practice in small− and large-group formats using three sample cases. The cases have been developed for the purposes of education and do not include actual patient information. Results This curriculum has been implemented in the current format with third− and fourth-year medical students as a 1-hour didactic near the end of the students' 6-week core rotation in psychiatry. A pilot group of nine students was surveyed both before and after the course to assess both need for a formal curriculum to teach assessment of decision-making capacity as well as the efficacy of this particular curriculum in improving learners' understanding of this topic. In the precourse survey, no student rated his or her confidence in assessing decision-making capacity as higher than 60%, and more than half of the students indicated that their confidence in evaluating decision-making capacity was 30% or less. No student was able to name all four elements that must be assessed in a decision-making capacity evaluation. Postcourse responses indicated substantial improvement in both objective and subjective realms. The majority of students (eight out of nine) now rated their confidence in assessing decision-making capacity as 60-100%. Seven out of nine students were able to identify all four essential elements of a capacity evaluation, and the remaining two students were able to identify three out of four essential elements. Discussion Both the primer and cases can also be used by students as reference materials after the course has been completed. Details regarding the nature of each individual component in the curriculum and recommendations for implementation can be found in the instructor's guide.